PARTICIPATIVE MANAGEMENT IN SCHOOLS: CONSOLIDATION OF DEMOCRACY AND ETHICS IN THE SCHOOL UNIT (International Seven Journal of Multidisciplinary, 2025)
Participatory school management is an educational organizational model focused on collective decision-making, guided by ethics, dialogue, and the appreciation of all segments of the school community. This article aims to analyze how participatory management can contribute to the consolidation of democracy and ethics in schools, based on a qualitative approach and methodologically grounded in bibliographic research. To this end, works by contemporary authors addressing democratic management, institutional ethics, and social participation in the educational context were consulted. Analysis of the selected material revealed that participatory management is an instrument of institutional transformation, as it promotes the active involvement of principals, teachers, students, parents, and other school stakeholders, strengthening a sense of belonging, shared responsibility, and transparency. It was also observed that participatory practices foster democratic coexistence, respect for diversity, ethical conflict resolution, and the development of critical citizens committed to the common good. The research also highlighted that, despite these positive contributions, structural challenges remain, such as a verticalized culture of power, a lack of training for participation, and the absence of effective institutional mechanisms. It concludes that the consolidation of participatory management requires investment in public policies, ongoing professional training, and the strengthening of spaces for democratic deliberation, such as school councils and assemblies. Participatory management, when implemented with authenticity and commitment, transforms the school into an ethical, democratic, and inclusive space, which contributes significantly to the comprehensive development of individuals and the strengthening of citizenship. By valuing listening, dialogue, and collective development, this management model reaffirms the role of the school as a formative environment focused on social transformation.